A biocompatible calcium carbonate-based liquid crystal material with electro-optical effect and preparation method and application thereof
Calcium carbonate-based liquid crystal materials prepared through gas diffusion reaction and cationic surfactant modification solve the problems of poor biocompatibility and high cost in traditional liquid crystal materials, and realize the preparation of low-cost, non-toxic and biocompatible liquid crystal materials for protein detection and biosensing.
Patent Information
- Application Number
- CN202310693213.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-06-13
Smart Images

Figure CN117089358B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation and application of special materials, and in particular to a biocompatible calcium carbonate-based liquid crystal material with electro-optical effect, and a preparation method and application thereof. Background Art
[0002] Liquid crystals are fluid but ordered molecular assemblies, and these self-assembled structures can be dynamically controlled by applying external stimuli such as electric and magnetic fields and mechanical forces to produce various functions. Although typical liquid crystals are based on rod-shaped and / or disc-shaped organic molecules, colloidal particles with controllable anisotropic morphology and size can also display liquid crystal (LC) phases in their dispersed state and are expected to have new functional properties. The production of functional materials from abundant resources using environmentally friendly processes is very important for the sustainable development of the future society. Calcium carbonate (CaCO3) is a major bio-friendly material. NAKAYAMA M et al (NAKAYAMA M, KAJIYAMA S, NISHIMURA T. Liquid-crystalline calcium carbonate: biomimetic synthesis and alignment of nanorod calcite [J]. Chemical Science, 2015, 6 (11): 6230-6234.; NAKAYAMA M, KAJIYAMA S, KUMAMOTO A. Bioinspired selective synthesis of liquid-crystalline nanocomposites: formation of calcium carbonate-based composite nanodisks and nanorods [J]. Nanoscale Advances, 2020, 2 (6): 2326-2332.) reported CaCO3-based liquid crystals formed by rod-like particles or disk-like particles. However, to the best of our knowledge, there are no reports on CaCO3 liquid crystal microspheres and fibrous CaCO3-based liquid crystal materials.
[0003] Understanding protein-surface interactions, which are mainly driven by non-covalent forces, forms the basis for developing the fundamental principles of intracellular biological processes and various biomedical applications. Given the fundamental importance of cooperative electrostatic interactions between proteins and other biomolecules / membranes in biological systems, it becomes crucial to design stimuli-responsive interfaces for protein adsorption and to identify the principles of such interactions between proteins and modified surfaces. Currently, there are many physicochemical methods available for detecting and studying protein interactions, such as affinity chromatography, protein arrays, surface plasmon resonance, quartz crystal microbalance, FTIR spectroscopy, NMR spectroscopy, and X-ray diffraction, but the expensive instrumentation and complexity limit their widespread use in daily life. Therefore, it is of great significance to develop a sensitive method that can respond to the electrostatic changes of biomolecules. Liquid crystal droplet microspheres have great potential as optical biosensors due to their tunable optical properties, large specific surface area, and rich optical configurations. VERMA I et al (VERMA I, SIDIQ S, PAL S K. Protein triggered ordering transitions in poly (L-lysine) -coated liquid crystal emulsion droplets [J]. Liquid Crystals, 2019, 46 (9): 1318-1326.) and BERA T et al (BERA T, DENG J, FANG J. Protein-Induced Configuration Transitions of Polyelectrolyte-Modified Liquid Crystal Droplets [J]. The Journal of Physical Chemistry B, 2014, 118 (18): 4970-4975) disclosed the use of 5-CB liquid crystal droplet microspheres for the detection of HSA and BSA, but 5-CB has high toxicity, poor biocompatibility, and high preparation cost. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a calcium carbonate-based liquid crystal material with electro-optical effect and biocompatibility, and a preparation method and application thereof. The calcium carbonate-based liquid crystal material prepared by the preparation method of the present invention is non-toxic, has good biocompatibility, and has low preparation cost.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect, comprising the following steps:
[0007] dissolving a water-soluble calcium salt to obtain a calcium salt solution;
[0008] Using ammonium carbonate as a diffusion gas source, the calcium salt solution undergoes a gas diffusion reaction to obtain a calcium carbonate liquid crystal microsphere system;
[0009] The calcium carbonate liquid crystal microsphere system is mixed with a cationic surfactant and modified to obtain the biocompatible calcium carbonate-based liquid crystal material with electro-optical effect.
[0010] Preferably, the dissolving reagent comprises a mixed solvent of water and ethylene glycol; the volume ratio of water to ethylene glycol in the mixed solvent of water and ethylene glycol is 1:3 to 1:6.
[0011] Preferably, the water-soluble calcium salt includes one or more of calcium chloride, calcium nitrate and calcium hydroxide, and the concentration of the calcium salt in the calcium salt solution is 30 to 50 mmol / L.
[0012] Preferably, the ratio of the amount of ammonium carbonate to the amount of calcium salt in the calcium salt solution is ≥1:1.
[0013] Preferably, the gas diffusion reaction time is 3h to 24h.
[0014] Preferably, the ratio of the amount of calcium carbonate microspheres to the amount of cationic surfactant in the mixed system is 1:5 to 1:10.
[0015] Preferably, the number of carbons in the carbon chain of the cationic surfactant is 16 to 18; the cationic surfactant includes one or more of hexadecyltrimethylammonium bromide, heptadecyltrimethylammonium bromide and N,N-dimethyl-N-octadecyl-3-aminopropyltrimethoxysilyl chloride.
[0016] Preferably, the modification temperature is room temperature and the modification time is 30 minutes to 1 hour.
[0017] The present invention also provides a biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect obtained by the preparation method described in the above technical solution.
[0018] The present invention also provides the application of the biocompatible calcium carbonate-based liquid crystal material with electro-optical effect described in the above technical solution in protein detection.
[0019] The invention provides a method for preparing a biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect, comprising the following steps: dissolving a water-soluble calcium salt to obtain a calcium salt solution; using ammonium carbonate as a diffusion gas source, the calcium salt solution undergoes a gas diffusion reaction to obtain a calcium carbonate liquid crystal microsphere system; and mixing the calcium carbonate liquid crystal microsphere system with a cationic surfactant for modification to obtain the biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect.
[0020] The present invention uses gas diffusion reaction to obtain calcium carbonate liquid crystal microspheres (CCT), which have excellent electro-optical effect and biocompatibility; the surface of CCT is modified by adsorption of cationic surfactants on the CCT / water interface, and the CCT modified by cationic surfactants are all radially configured and have positive charges. Negatively charged serum albumin (HSA and BSA) is adsorbed on the CCT modified by the positively charged cationic surfactant through a force dominated by electrostatic action, which can induce the radial-bipolar configuration transformation of small particles inside the CCT. The data of the embodiment show that: under the modification of CTAB with a concentration of 1mM, the concentration of HSA and BSA required to induce the configuration transformation of CCT can be as low as 5μg / mL, and the response time is 25min, highlighting the ability of the director configuration of CCT as an optical probe to detect the interaction between proteins and surfactants at the CCT / water interface. And the good cell compatibility of CTAB-CCT is proved by experiments, and it is successfully applied to the imaging of HSA outside living cells. In future work, a certain concentration of HSA can be added to the cell culture medium, and then CTAB-CCT can be incubated with different types of cells for the same time. After the cells have taken up a portion of HSA, the configuration conversion rate of CTAB-CCT can be used to reflect the remaining HSA concentration in the extracellular culture medium. Because different types of cells have different abilities to take up HSA, this result can be used to distinguish cell lines and explore cell heterogeneity. CTAB-CCT can map and distinguish physiologically important concentration ranges by the percentage of its configuration transition. In addition, the detection limit of HSA has reached 5μg / mL. CTAB-CCT was incubated with MCF-7 cells, and the survival rate of MCF-7 cells was as high as 99.9%, which proved its good biocompatibility and laid the foundation for subsequent live cell extracellular imaging. After that, different concentrations of HSA were added to the external environment of MCF-7 cells, and CTAB-CCT was added for co-incubation. The configuration conversion of CTAB-CCT was observed under POM, which proved the ability of modified calcium carbonate liquid crystal microspheres to image biomacromolecules in the extracellular environment of living cells. CTAB-CCT has the advantages of controllable size, good cell compatibility, high sensitivity, and easy detection by POM. At the same time, the calcium carbonate-based liquid crystal material with electro-optical effect and biocompatibility prepared by the present invention has a series of advantages such as green, non-toxic, low cost, and renewable compared with traditional liquid crystal materials such as 5-CB and E7.
[0021] The present invention also provides a biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect obtained by the preparation method described in the above technical solution. The calcium carbonate-based liquid crystal material provided by the present invention can respond to external electric fields and mechanical shear forces, and can be used to detect proteins, such as human serum albumin. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The performance characterization diagrams of calcium carbonate substances obtained by gas diffusion reaction for 30 minutes, wherein (a) is a TEM image of calcium carbonate substances, (b) is a POM image of calcium carbonate substances, and (c) is a microscope image of calcium carbonate substances;
[0023] Figure 2 The figures are scanning electron microscope (SEM) images and corresponding microscope images of calcium carbonate substances obtained after gas diffusion reaction at different times, wherein (a) is a SEM image of calcium carbonate substances obtained after gas diffusion reaction for 1 hour, (d) is a microscope image of calcium carbonate substances obtained after gas diffusion reaction for 1 hour, (b) is a SEM image of calcium carbonate substances obtained after gas diffusion reaction for 4 hours, (e) is a microscope image of calcium carbonate substances obtained after gas diffusion reaction for 4 hours, (c) is a SEM image of calcium carbonate substances obtained after gas diffusion reaction for 6 hours, and (f) is a microscope image of calcium carbonate substances obtained after gas diffusion reaction for 6 hours;
[0024] Figure 3 The polarized light microscope (POM) images and corresponding microscope images of calcium carbonate substances obtained after gas diffusion reaction at different times, wherein (a) is a POM image of calcium carbonate substances obtained after gas diffusion reaction for 3 hours, (d) is a microscope image of calcium carbonate substances obtained after gas diffusion reaction for 3 hours, (b) is a POM image of calcium carbonate substances obtained after gas diffusion reaction for 12 hours, (e) is a microscope image of calcium carbonate substances obtained after gas diffusion reaction for 12 hours, (c) is a POM image of calcium carbonate substances obtained after gas diffusion reaction for 24 hours, and (f) is a microscope image of calcium carbonate substances obtained after gas diffusion reaction for 24 hours;
[0025] Figure 4 The POM images of calcium carbonate obtained by gas diffusion reaction for 24 hours at different angles of the polarizer;
[0026] Figure 5 The POM diagrams are of the calcium carbonate liquid crystal microsphere system obtained by gas diffusion reaction for 24 hours, which is dispersed in ethylene glycol to prepare systems with different concentrations, wherein (a) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 5%, (b) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 10%, (c) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 30%, and (d) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 35%;
[0027] Figure 6 Schematic diagram of the synthesis of calcium carbonate colloidal liquid crystals for a biomineralization-inspired approach;
[0028] Figure 7The POM diagrams of the precipitates obtained after the gas diffusion reaction at different times, wherein (a) is the POM diagram of the precipitate obtained after the gas diffusion reaction for 30 minutes, (b) is the POM diagram of the precipitate obtained after the gas diffusion reaction for 3 hours, and (c) is the POM diagram of the precipitate obtained after the gas diffusion reaction for 24 hours;
[0029] Figure 8 This is a schematic diagram of calcium carbonate gel being placed upside down in a centrifuge tube;
[0030] Fig. 9 Characterization diagrams of the precipitate obtained after 24 hours of gas diffusion reaction, wherein (a) is a TEM image of the precipitate obtained, (b) is a SEM image of the precipitate obtained, (c) is a POM image of the precipitate obtained, (d) is a TEM image of a single calcium carbonate fiber, (e) is a HRTEM image of the calcium carbonate fiber, and (f) is a SAED image of the calcium carbonate fiber;
[0031] Fig.10 The POM image and microscope image of the calcium carbonate colloidal liquid crystal coated on the rubbed PI film, wherein (a) is the POM image and (b) is the microscope image;
[0032] Fig.11 The polarization morphology of calcium carbonate colloidal liquid crystal under different electric field strengths;
[0033] Fig.12 It is the performance characterization diagram of a single CCT;
[0034] Fig.13 POM images of CCT dispersed in different solutions: (a) dispersed in water, (b) dispersed in DMF, and (c) dispersed in PBS buffer;
[0035] Fig.14 Two different orientation diagrams of CCT: (a) is the bipolar conformation, (b) is the radial conformation, (i) (iv) are schematic diagrams of the two conformations, (ii) (v) are photos of the two conformations under POM, and (iii) (vi) are photos of the two conformations under a microscope;
[0036] Fig.15 Two configurations of CCT characterized by SEM, where (a) is radial configuration and (b) is bipolar configuration;
[0037] Fig.16 Schematic diagram and optical images of CCT configuration under the action of different surfactants;
[0038] Fig.17To add different concentrations of surfactant CTAB to CCT, (a) is the POM image of CTAB concentration of 1mM, (e) is the microscope image of CTAB concentration of 1mM, (b) is the POM image of CTAB concentration of 10mM, (f) is the microscope image of CTAB concentration of 10mM, (c) is the POM image of CTAB concentration of 20mM, (g) is the microscope image of CTAB concentration of 20mM, (d) is the POM image of CTAB concentration of 30mM, (h) is the microscope image of CTAB concentration of 30mM;
[0039] Fig.18 POM images of CCT modified with CTAB before (a) and after (b) washing with DMF three times;
[0040] Fig.19 POM images of CCT modified with PVA before (a) and after (b) washing with DMF three times;
[0041] Fig. 20 POM images and microscope images of CTAB-CCTs in PBS buffers with different pH values: (a) POM image at pH = 5, (c) POM image at pH = 7.4, (e) POM image at pH = 9.8, (g) POM image at pH = 12.2: (b) microscope image at pH = 5, (d) microscope image at pH = 7.4, (f) microscope image at pH = 9.8, (h) microscope image at pH = 12.2;
[0042] Fig.21 Schematic diagram of the CCT surface configuration transformation in a high pH buffer environment;
[0043] Fig. 22 This is a schematic diagram of the working principle of the CCT-based biosensor;
[0044] Fig.23 Optical images of CTAB-CCT before and after adding 1 mg / mL HSA solution (a) and Zeta potential images of CTAB-CCT and after adding HSA / BSA (each 1 mg / mL) (b);
[0045] Fig.24 CLSM images (a) and fluorescence intensity diagram (b) after incubation of CTAB-CCTs with 1 mg / mL FITC-labeled HSA;
[0046] Fig.25 POM images of the radial-bipolar configuration and the intensity distribution of the radial-bipolar deformation of CTAB-CCTs after exposure to HSA buffer at pH = 7.4 for different time periods;
[0047] Fig.26POM images and microscope bright field images of CTAB-CCTs after exposure to HSA solutions of different concentrations:
[0048] Fig. 27 The configuration conversion rate of CTAB-CCTs exposed to HSA buffer solutions with different concentrations (a) and the calibration curve of HSA concentration obtained using the configuration conversion rate of CTAB-CCTs (mean standard deviation, n=3) (b);
[0049] Fig.28 POM images and corresponding bright field microscopy images of CTAB-CCTs exposed to 1 mg / mL buffer solutions of different substances, where (a) and (e) are Na + , (b) and (f) are Fe 2+ , (c) and (g) are glucose, (d) and (h) are L-glutamine, (i) and (k) are HSA, and (j) and (l) are BSA;
[0050] Fig.29 This is a graph showing the survival of MCF-7 cells before and after the addition of CTAB-CCTs;
[0051] Fig.30 The images show CTAB-CCTs imaging different concentrations of HSA outside MCF-7 cells. DETAILED DESCRIPTION
[0052] The present invention provides a method for preparing a biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect, comprising the following steps:
[0053] dissolving a water-soluble calcium salt to obtain a calcium salt solution;
[0054] Using ammonium carbonate as a diffusion gas source, the calcium salt solution undergoes a gas diffusion reaction to obtain a calcium carbonate liquid crystal microsphere system;
[0055] The calcium carbonate liquid crystal microsphere system is mixed with a cationic surfactant and modified to obtain the biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect.
[0056] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0057] The present invention dissolves water-soluble calcium salt to obtain a calcium salt solution.
[0058] In the present invention, the water-soluble calcium salt preferably includes one or more of calcium chloride, calcium nitrate and calcium hydroxide, and more preferably calcium chloride. In the present invention, the dissolving reagent preferably includes a mixed solvent of water and ethylene glycol; the volume ratio of water to ethylene glycol in the mixed solvent of water and ethylene glycol is preferably 1:3 to 1:6, and more preferably 1:4 to 1:5. In the present invention, the concentration of calcium salt in the calcium salt solution is preferably 30 to 50 mmol / L. In the present invention, the dissolution is preferably carried out under stirring conditions. The present invention does not specifically limit the rotation speed of the stirring, as long as the water-soluble calcium salt can be dissolved.
[0059] After obtaining the calcium salt solution, the present invention uses ammonium carbonate as a diffusion gas source, and the calcium salt solution undergoes a gas diffusion reaction to obtain a calcium carbonate liquid crystal microsphere system.
[0060] In the present invention, the ratio of the amount of the ammonium carbonate to the amount of the calcium salt in the calcium salt solution is preferably ≥ 1:1. In the present invention, the temperature of the gas diffusion reaction is preferably room temperature, that is, no additional heating or cooling is required; the time of the gas diffusion reaction is preferably 3 to 24 hours. In a specific embodiment of the present invention, the specific process of the gas diffusion reaction is preferably: placing ammonium carbonate on the outer periphery of the bottom of a large beaker, placing a calcium salt solution in a small beaker, and placing the small beaker containing the calcium salt solution in the middle of the large beaker, sealing the large beaker, and performing a gas diffusion reaction.
[0061] After the gas diffusion reaction, the present invention preferably includes: centrifuging the product obtained by the gas diffusion reaction, and taking the lower layer of liquid as a calcium carbonate liquid crystal microsphere system for subsequent reaction.
[0062] After the calcium carbonate liquid crystal microsphere system is obtained, the calcium carbonate liquid crystal microsphere system is mixed with a cationic surfactant and modified to obtain the biocompatible calcium carbonate-based liquid crystal material with electro-optical effect.
[0063] In the present invention, the number of carbons in the carbon chain of the cationic surfactant is preferably 16 to 18; the cationic surfactant further preferably includes one or more of hexadecyltrimethylammonium bromide, heptadecyltrimethylammonium bromide and N,N-dimethyl-N-octadecyl-3-aminopropyltrimethoxysilyl chloride, more preferably hexadecyltrimethylammonium bromide (CTAB). In the present invention, the ratio of the amount of calcium carbonate microspheres and the cationic surfactant in the mixed system is preferably 1:5 to 1:10. In the present invention, the concentration of the cationic surfactant in the mixed system is preferably 1 mM. In the present invention, the modification temperature is preferably room temperature, that is, neither additional heating nor additional cooling is required; the modification time is preferably 30 min to 1 h.
[0064] The present invention also provides a biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect obtained by the preparation method described in the above technical solution.
[0065] The present invention also provides the application of the biocompatible calcium carbonate-based liquid crystal material with electro-optical effect described in the above technical solution in protein detection.
[0066] The calcium carbonate-based liquid crystal material provided by the present invention can respond to external electric fields and mechanical shear forces, and can be used to detect proteins, such as human serum albumin (HSA) or bovine serum albumin (BSA).
[0067] In the present invention, when the biocompatible calcium carbonate-based liquid crystal material with electro-optical effect is applied to protein detection, the pH value is preferably controlled to be 7 to 7.4. In the present invention, the protein preferably includes human serum albumin (HSA) or bovine serum albumin (BSA).
[0068] The biocompatible calcium carbonate-based liquid crystal material with electro-optical effect provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0069] Example 1
[0070] Prepare a solution with a volume ratio of 1:5 between water and ethylene glycol in a beaker, stir evenly, and obtain a mixed solvent. Weigh a certain weight of calcium chloride dihydrate, and use the mixed solvent obtained above to prepare a calcium chloride solution with a concentration of 50mM. Place the calcium chloride solution in a constant temperature device, and set the temperature to 30°C. Spread a circle of ammonium carbonate around the beaker (the molar ratio of carbonate in ammonium carbonate to calcium chloride in calcium chloride solution is 1:1), and perform gas diffusion reaction for different times. After the gas diffusion reaction is completed, centrifuge and wash the resulting precipitate to obtain calcium carbonate substances.
[0071] Figure 1 The performance characterization diagrams of calcium carbonate materials obtained by gas diffusion reaction for 30 minutes, wherein (a) is a TEM image of calcium carbonate materials, (b) is a POM image of calcium carbonate materials, and (c) is a microscope image of calcium carbonate materials. Figure 1 It can be seen that calcium carbonate particles with a size of tens of nanometers were generated. At this time, the particles were irregular in shape and had a certain aspect ratio. They were characterized by polarizing microscopy (POM) and optical microscopy. They showed a dark field under the POM field of view, indicating that the calcium carbonate particles were in an isotropic state in the solution.
[0072] The products of the gas diffusion reaction at different times were dropped onto a glass slide, dried with nitrogen, and characterized using a scanning electron microscope (SEM) and an optical microscope. The results are shown in Figure 2. Figure 2As shown, (a) is a SEM image of the calcium carbonate-like substance obtained after 1 hour of gas diffusion reaction, (d) is a microscope image of the calcium carbonate-like substance obtained after 1 hour of gas diffusion reaction, (b) is a SEM image of the calcium carbonate-like substance obtained after 4 hours of gas diffusion reaction, (e) is a microscope image of the calcium carbonate-like substance obtained after 4 hours of gas diffusion reaction, (c) is a SEM image of the calcium carbonate-like substance obtained after 6 hours of gas diffusion reaction, and (f) is a microscope image of the calcium carbonate-like substance obtained after 6 hours of gas diffusion reaction. Figure 2 As shown in (a) and (d) in the figure, when the gas diffusion reaction time is 1 hour, due to the short reaction time, the CaCO3 particles generated in the solution are relatively small, and these particles assemble into agglomerates with uniform size and a particle size of about 1 μm. When the gas diffusion reaction time is 4 hours, as time goes by, the number of CaCO3 particles generated in the solution gradually increases, and they self-assemble into agglomerates with a particle size of about 5 μm (such as Figure 2 As shown in (b) and (e) of Figure 2 As shown in (c) and (f), when the gas diffusion reaction time reaches 6h, the particle size of the agglomerate particles reaches about 10μm, and fusion occurs. It can be seen that the shapes of these agglomerates are very irregular.
[0073] The products of the gas diffusion reaction after different times were placed under POM for observation. The results are as follows: Figure 3 As shown, Figure 3 Among them, (a) is a POM image of the calcium carbonate-like substance obtained after 3 hours of gas diffusion, (d) is a microscope image of the calcium carbonate-like substance obtained after 3 hours of gas diffusion, (b) is a POM image of the calcium carbonate-like substance obtained after 12 hours of gas diffusion, (e) is a microscope image of the calcium carbonate-like substance obtained after 12 hours of gas diffusion, (c) is a POM image of the calcium carbonate-like substance obtained after 24 hours of gas diffusion, and (f) is a microscope image of the calcium carbonate-like substance obtained after 24 hours of gas diffusion. Figure 3 It can be observed that the aggregate particles can reflect polarized light and show a unique optical morphology. Figure 3 As shown in (a) and (d) in the figure, after 3 hours of reaction, the particle size of the generated particles is about 5μm, and there are two polarized optical morphologies, namely, "black cross" extinction shape and ellipsoid shape. This is consistent with the characteristics of tactoid aggregates, so it is speculated that the generated CaCO3 aggregate particles are a type of tactoid. As the reaction time increases, reaching 12 hours, as shown in Figure 3 As shown in (b), the tactoids in the solution will fuse with each other and combine with the newly generated nano-CaCO3 particles, becoming larger and larger, forming dumbbell-shaped aggregates with a length of about 50 μm (such as Figure 3 As shown in (e)). Figure 3As shown in (c) and (f) of FIG. 5 , after 24 h of reaction, obvious birefringence textures appeared in the field of view of polarizing microscope, which indicated the formation of liquid crystal (LC) phase.
[0074] Figure 4 The POM images of calcium carbonate obtained by gas diffusion reaction for 24 hours under different polarizer angles are shown in Figure 1. Figure 4 It can be observed that this birefringence phenomenon still exists when the polarizer is adjusted to different angles. Nayani et al. believe that when the isotropic phase of the lyotropic system undergoes a phase transition to an ordered liquid crystal phase, this pathway is usually mediated by droplets called tactoids. This phenomenon confirms our conjecture and also explains the CaCO3tactoid (CCT) morphology that appears after 3h of reaction.
[0075] The product obtained by gas diffusion reaction for 24 hours was centrifuged, and the lower layer of liquid was collected as a calcium carbonate liquid crystal microsphere system. The obtained calcium carbonate liquid crystal microsphere system was prepared into systems of different concentrations with ethylene glycol and POM observation was performed. The results are as follows Figure 5 As shown, Figure 5 Among them, (a) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 5%, (b) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 10%, (c) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 30%, and (d) is the POM diagram of the calcium carbonate liquid crystal microsphere system with a volume concentration of 35%. Figure 5 The morphology of nano-calcium carbonate with different concentrations dispersed in ethylene glycol solution is shown in Figure 2. Figure 5 As shown in the figure, CaCO3 crystallizes in ethylene glycol (EG) / water (5:1) solution to form nanospheres, and the colloidal dispersion of these nanoparticles exhibits a liquid crystal state. This is because the shape anisotropy of the CaCO3 nanospheres leads to the liquid crystal characteristics in the dense colloidal dispersion system. As the reaction time increases, more and more nano-CaCO3 is generated in the system and will assemble into aggregates of different forms. The aqueous colloidal dispersion of CaCO3 nanospheres reacted in the solution for different times was observed using POM; when the reaction time was 30 minutes, a dark image (such as Figure 1 (b) shows that the CaCO3 nanospheres are isotropic in the colloidal dispersion; when the reaction time is 3h, the CCT of the two-phase coexistence state is observed (as shown in Figure 3 When the reaction time is increased to more than 24 h, the liquid crystal texture of the entire region is observed under POM (as shown in (a)). Figure 3 (c)). The average Zeta potential of CaCO3 nanospheres was measured to be -13.8 mV, so the surface of these materials is negatively charged. It is further believed that the EG molecules cover the surface of the nanoparticles to provide colloidal stability, which is important for the formation of colloidal liquid crystal state.
[0076] Figure 6 Schematic diagram of the synthesis of calcium carbonate colloidal liquid crystals for a biomineralization-inspired approach, e.g. Figure 6 As shown, the nano-CaCO3 particles prepared by the biomineralization-inspired method can self-assemble into different forms in the solution, thereby completing the three-phase phase transition process of colloidal liquid crystal, namely, the isotropic phase, the two-phase coexistence phase and the liquid crystal phase.
[0077] The products obtained after 30 min, 3 h and 24 h of gas diffusion reaction were centrifuged, and the lower layer of liquid was collected as the calcium carbonate liquid crystal microsphere system. The mouth of the cup was sealed with plastic wrap. After 7 days, the supernatant was poured out, and the sediment at the bottom of the beaker was retained. POM observation was performed. The results are as follows Figure 7 As shown, (a) is the POM diagram of the sediment obtained after 30 minutes of gas diffusion reaction, (b) is the POM diagram of the sediment obtained after 3 hours of gas diffusion reaction, and (c) is the POM diagram of the sediment obtained after 24 hours of gas diffusion reaction. Figure 7 It can be seen that: (a) is the isotropic phase; (b) is the two-phase coexistence phase; (c) is the liquid crystal phase.
[0078] The product obtained by the gas diffusion reaction for 24 hours was centrifuged, and the lower layer of liquid was collected as the calcium carbonate liquid crystal microsphere system. The cup mouth was sealed with plastic wrap. After leaving it for 7 days, the supernatant was poured out and the cup was inverted. The results were as follows: Figure 8 As shown, Figure 8 Schematic diagram of calcium carbonate gel placed upside down in a centrifuge tube. Figure 8 It can be seen that: unlike the granular state of ordinary CaCO3 precipitate, the product at the bottom of the cup is collected and stored in a centrifuge tube, which is placed upside down. It can be seen that the product is in a gel state.
[0079] In order to further understand the structure of this CaCO3 gel, the product obtained by the gas diffusion reaction for 24 hours was centrifuged, and the lower layer of liquid was collected as the calcium carbonate liquid crystal microsphere system. The mouth of the cup was sealed with plastic wrap. After leaving it for 7 days, the supernatant was poured out and the obtained sediment was characterized. The results are as follows Fig. 9 As shown, (a) is a TEM image of the obtained sediment, (b) is a SEM image of the obtained sediment, (c) is a POM image of the obtained sediment, (d) is a TEM image of a single calcium carbonate fiber, (e) is a HRTEM image of the calcium carbonate fiber, and (f) is a SAED image of the calcium carbonate fiber. Fig. 9 As shown in (a) and (b), it can be clearly seen that the sediment is composed of long nanofibers with a fiber length of about 500nm. These nanofibers are crisscrossed to form a complex network structure. Fig. 9 As shown in (c), the resulting precipitate exhibits a typical birefringent texture under POM. The gelation of CaCO3 liquid crystal is due to the Ca2+ EG molecules cross-link with CaCO3 particles that have formed a colloidal liquid crystal phase. 2+ In the system, it combines with calcium carbonate particles with -OH on the surface as cross-linking sites, thus forming a network structure and enhancing the strength of the system. Fig. 9 As shown in (d), the structure of a single calcium carbonate fiber was analyzed. Fig. 9 As shown in (e), the nanofibers were characterized by HRTEM. After comparing with the theoretical interplanar spacing, the yellow arrow indicates the (114) crystal plane of vaterite-type CaCO3. Fig. 9 As shown in (f), the arch pattern observed in the selected area electron diffraction (SAED) pattern indicates that the structure of the CaCO3 nanofibers is crystallographically oriented.
[0080] The product obtained by the gas diffusion reaction for 24 hours was centrifuged, and the lower layer of liquid was collected as the calcium carbonate liquid crystal microsphere system. The cup mouth was sealed with plastic wrap. After 7 days, the supernatant was poured out, and the obtained sediment was prepared into 35 vol% calcium carbonate colloidal liquid crystal with ethylene glycol. The 35 vol% calcium carbonate colloidal liquid crystal was coated on the rubbed PI film along the rubbing direction and observed. The results are as follows: Fig.10 As shown in Figure 1, (a) is a POM image and (b) is a microscope image. Fig.10 As shown, a polyimide (PI) film is rubbed with silk, and the concentration of calcium carbonate colloidal liquid crystal obtained by reaction for 24 hours is configured to 35%, and the CaCO3 colloidal liquid crystal is coated on the film along the rubbing direction. It can be observed through POM that the CaCO3 colloidal liquid crystal appears dark in the field of view of POM.
[0081] Afterwards, 35 vol% of calcium carbonate colloidal liquid crystal was coated on the surface of the interdigital electrode, and an adjustable power supply was used to apply voltages of different strengths across the electrodes. The results were as follows: Fig.11 As shown, Fig.11 The polarization morphology of calcium carbonate colloidal liquid crystal under different electric field strengths; Fig.11 It can be seen that as the voltage gradually increases from 0V to 30V, the morphology of the liquid crystal between the electrodes gradually changes from bright to dark under the field of view of the POM, which indicates that the liquid crystal changes from an optical anisotropy state to an isotropy state. And when the voltage reaches 30V, the response time is within 1s. These phenomena together illustrate that the CaCO3 colloidal liquid crystal has electric field response characteristics.
[0082] The product obtained by the gas diffusion reaction for 3 hours was centrifuged, and the lower layer of liquid was collected as the calcium carbonate liquid crystal microsphere system, which was subjected to a series of characterizations. The results are as follows Fig.12 As shown, Fig.12 is the performance characterization diagram of a single CCT. Fig.12In the figure, (a) is a SEM image of a single CCT, (b) is a locally enlarged SEM image of a single CCT, (c) is a POM image of a single CCT, (d) is a bright field microscope image of a single CCT, (e) is an X-ray diffraction (XRD) image of the CCT, (f) is a Raman spectrum image of the CCT, (g) is a wide angle diffraction (WAXS) 2D image of the CCT, and (h) is a wide angle diffraction (WAXS) image of the CCT. Fig.12 As shown in (a) and (b), CCT is composed of single crystalline subunits that are arranged in a certain order, giving it an overall birefringent property, showing a classic "Maltese cross" morphology under POM ( Fig.12 (c) and (d)). Fig.12 As shown in (e) and (f), according to the characterization results of Raman spectroscopy and X-ray diffractometer, the nano-sized calcium carbonate crystals that constitute CCT are vaterite. Fig.12 As shown in (g) and (h), wide-angle diffraction (WAXS) tests show that the arrangement inside the CCT is highly ordered in different directions.
[0083] The product obtained by the gas diffusion reaction for 3 h was centrifuged, and the lower layer of liquid was collected as a calcium carbonate liquid crystal microsphere system, and the calcium carbonate liquid crystal microsphere system was dispersed in different solvents, such as Fig.13 As shown, Fig.13 Polarized optical microscope (POM) images of CCT dispersed in different solutions: (a) dispersed in water; (b) dispersed in DMF; (c) dispersed in PBS buffer. Fig.13 As shown in the figure, in water, CCT will connect into a large piece; in DMF, CCT can continue to maintain its monodisperse droplet morphology; similarly, in PBS with a pH value of 7.4, CCT can also maintain a monodisperse state, which lays the foundation for subsequent biological applications.
[0084] The product obtained by the gas diffusion reaction for 3 hours was centrifuged, and the lower layer of liquid was collected as the calcium carbonate liquid crystal microsphere (CCT) system. The parallel orientation and vertical orientation of CCT in three-dimensional morphology were called biopolar orientation (B) and radial orientation (R), respectively. Fig.14 As shown, Fig.14 Two different orientation diagrams of CCT: Fig.14In the figure, (a) is a bipolar conformation, (b) is a radial conformation, (i) (iv) are schematic diagrams of the two conformations, (ii) (v) are photos of the two conformations under POM, and (iii) (vi) are photos of the two conformations under a microscope. When observed under POM, the radial orientation shows a single point defect at the center, while the bipolar orientation shows defects on both sides at the two poles. It is further believed that the reason for the difference in the two configurations is mainly due to the different arrangement of the particles that constitute CCT. It is because of this difference that the optical morphology is different in the macroscopic sense.
[0085] Next, the calcium carbonate liquid crystal microsphere (CCT) system was dripped onto the silicon wafer and waited for it to dry. Then, two representative configurations of CCT (radial configuration and bipolar configuration) were characterized by SEM. Fig.15 As shown, Fig.15 Two configurations of CCT characterized by SEM, where (a) is radial configuration and (b) is bipolar configuration; Fig.15 As shown in (a), it can be observed that in the radially configured CCT under POM, the nano-CaCO3 particles constituting the CCT are arranged radially outward from the center of the CCT. Fig.15 In the plane shown in (a), the particle arrangement direction is marked by red arrows. Fig.15 In (b), it can be clearly observed that the nano-CaCO3 particles on the surface of the bipolar CCT are arranged in the same direction. If you zoom in on the part, you can see that the particles are arranged in the direction marked by the red arrow. This result confirms our conjecture about the reason why the two configurations of CCT have different optical morphologies in the macroscopic sense.
[0086] Example 2
[0087] Prepare a solution with a volume ratio of 1:5 between water and ethylene glycol in a beaker, stir evenly to obtain a mixed solvent. Weigh a certain weight of calcium chloride dihydrate, and use the mixed solvent obtained above to prepare a calcium chloride solution with a concentration of 50mM. Place the calcium chloride solution in a constant temperature device and set the temperature to 30°C. Spread a circle of ammonium carbonate around the beaker (the molar ratio of carbonate in ammonium carbonate to calcium chloride in calcium chloride solution is 1:1), and perform gas diffusion reaction for 3 hours to obtain gas diffusion products; centrifuge the gas diffusion products, and take the lower layer of solution as the calcium carbonate liquid crystal microsphere system.
[0088] 2.1 Experimental study on the effect of different surfactants on CCT
[0089] A certain concentration of hexadecyltrimethylammonium bromide (CTAB) solution and polyvinyl alcohol (PVA) solution were prepared with PBS at a pH of 7.4. CTAB solution and PVA solution were added to the calcium carbonate liquid crystal microsphere system, and the final concentrations of CTAB and PVA in the mixed system were 1mM, and the concentration of the calcium carbonate liquid crystal microspheres was 0.2mM. The modification was carried out for 30 minutes. The samples were dropped onto glass slides and the phenomena were observed under an optical microscope and a polarizing microscope.
[0090] 2.2 Experiment on the effect of different concentrations of CTAB on CCT
[0091] A series of CTAB solutions with different concentrations were prepared using PBS with a pH value of 7.4 and added to the calcium carbonate liquid crystal microsphere system. In the mixed system, the concentration of the calcium carbonate liquid crystal microspheres was 0.2 mM, and the concentrations of CTAB were 1 mM, 10 mM, 20 mM and 30 mM, respectively. The system was magnetically stirred for 30 minutes, and the experimental phenomena were observed.
[0092] 2.3 Elution experiment of surfactant-modified CCT
[0093] The CCTs modified with surfactant at a concentration of 1 mM in step 2.2 were collected in a 10 mL centrifuge tube, centrifuged and the precipitate was collected. The precipitate was then washed three times with DMF at 5000 r / min for 6 min, and then redispersed in PBS and observed under a polarizing microscope.
[0094] 2.4 Experiment on the effect of different environmental pH values on CTAB-CCT
[0095] The pH value of PBS was adjusted with disodium hydrogen phosphate and sodium dihydrogen phosphate solutions, and after adjusting to different pH values, CTAB-modified CCT particles were added at a final concentration of 100 μg / mL. The CTAB-modified CCT particles were incubated in PBS for 30 minutes, and the solution was taken out with a dropper and dropped onto a glass slide, which was then placed under an optical microscope and a polarizing microscope to observe the phenomenon.
[0096] Fig.16 Schematic diagram and optical image of CCT configuration under the action of different surfactants, such as Fig.16As shown in the figure, CCT particles modified with 1 mM amphiphilic surfactant polyvinyl alcohol (PVA) exhibit a "hollow" morphology under POM. However, CCT particles modified with 1 mM cationic surfactant hexadecyl ammonium bromide (CTAB) almost all exhibit the expected typical "Maltese cross" morphology, showing a radial configuration. This configuration transformation of CCT particles modified with PVA is caused by the complex energy pattern of the arrangement of small particles inside. The bipolar configuration produced by the modification of PVA is an energy deformation caused by its adsorption on the surface of CCT particles, which causes the interface to bend. This configuration has higher energy than the radial configuration. However, CCT particles modified with CTAB all become radial configurations. This is because CTAB self-assembles at the CCT / water interface, directs the hydrophilic -OH group to the water medium, and embeds the hydrophobic part into CCT. It is precisely because the CTAB molecule has a hydrophilic head and a hydrophobic alkyl chain tail that it can stabilize this radial configuration. Finally, the surfactant CTAB was selected to participate in the construction of CCT-based optical sensor.
[0097] Fig.17 In order to add different concentrations of surfactant CTAB into CCT, Fig.17 In the figure, (a) is a POM image with a CTAB concentration of 1 mM, (e) is a microscope image with a CTAB concentration of 1 mM, (b) is a POM image with a CTAB concentration of 10 mM, (f) is a microscope image with a CTAB concentration of 10 mM, (c) is a POM image with a CTAB concentration of 20 mM, (g) is a microscope image with a CTAB concentration of 20 mM, (d) is a POM image with a CTAB concentration of 30 mM, and (h) is a microscope image with a CTAB concentration of 30 mM. Fig.17 As shown in the figure, CTAB at a suitable concentration, such as 1mM, can induce the CCT with two optical configurations coexisting under the initial condition to transform into a radial configuration. When the CTAB concentration increases to 10mM, the CCT loses the "black cross" polarization morphology under POM. As the CTAB concentration increases, the volume of the CCT becomes smaller and smaller. When the concentration increases to 30mM, the volume reaches the minimum. Therefore, in subsequent experiments, CTAB with a concentration of 1mM was selected to modify the CCT to achieve the best effect.
[0098] Fig.18 POM images of CCT modified with CTAB before (a) and after (b) washing with DMF three times. Under POM, Fig.18As shown in (a), after CCT was modified with 1 mM CTAB, the particles all showed a radial configuration, which was different from the coexistence of the two configurations before modification. After washing with DMF three times, we found that the CCT at this time did not present a single configuration as before washing, but was consistent with the configuration of CCT before CTAB modification, that is, the two configurations coexisted ( Fig.18 The elution experiment proves that the CTAB molecules adsorbed on the CCT surface can be detached by washing with DMF.
[0099] Next, the elution experiment of PVA-modified CCT was conducted. Fig.19 POM images of the CCT of PVA modified with DMF before (a) and after (b) washing for 3 times. Fig.19 As shown in the figure, after CCT was modified with PVA at the same concentration of 1mM, it was observed under POM, and it was found that the center of CCT showed a black vacancy. Then, it was washed three times with DMF, and it was found that under the POM field of view, the black defect in the middle of CCT disappeared, and the appearance before PVA modification was restored. The elution experiment using DMF showed that PVA was only adsorbed on the surface of CCT and did not destroy the structure of CCT. The elution experiment also showed that CCT has the ability to be reused.
[0100] Finally, the effect of environmental pH on CTAB-modified CCT (CTAB-CCT) was studied. Fig. 20 As shown, Fig. 20 POM images and microscope images of CTAB-CCTs in PBS buffers with different pH values: (a) POM image at pH = 5, (c) POM image at pH = 7.4, (e) POM image at pH = 9.8, (g) POM image at pH = 12.2: (b) microscope image at pH = 5, (d) microscope image at pH = 7.4, (f) microscope image at pH = 9.8, (h) microscope image at pH = 12.2; Fig. 20 As shown in the figure, at pH = 5, most of the CTAB-CCTs are dissolved and connected into a large piece. This is because CaCO3 cannot exist stably in an acidic environment; when pH = 7.4, all CTAB-CCTs present a radial configuration; and when pH ≥ 9.8, almost all CTAB-CCTs present a bipolar configuration.
[0101] Fig.21 Schematic diagram of the CCT surface configuration transformation in a high pH buffer environment. Fig.21As shown in Figure 2, it is known that CCT particles are synthesized in an aqueous solution of ethylene glycol, and their structure contains a large number of alcoholic hydroxyl groups. Alcoholic hydroxyl groups are deprotonated under the action of alkali, so it is believed that the radial-bipolar change of CCT droplets under alkaline conditions is attributed to the deprotonation of -OH in CCT. The -OH contained in the CCT droplet structure is a pH-sensitive functional group, and it is precisely because of its existence that the orientation of CCT is pH-responsive.
[0102] Example 3
[0103] Prepare a solution with a volume ratio of 1:5 between water and ethylene glycol in a beaker, stir evenly to obtain a mixed solvent. Weigh a certain weight of calcium chloride dihydrate, and use the mixed solvent obtained above to prepare a calcium chloride solution with a concentration of 50mM. Place the calcium chloride solution in a constant temperature device and set the temperature to 30°C. Spread a circle of ammonium carbonate around the beaker (the molar ratio of carbonate in ammonium carbonate to calcium chloride in calcium chloride solution is 1:1), and perform gas diffusion reaction for 3 hours to obtain gas diffusion products; centrifuge the gas diffusion products, and take the lower layer of solution as the calcium carbonate liquid crystal microsphere system.
[0104] CTAB was prepared with a PBS solution at pH = 7.4 to obtain a uniform solution with a concentration of 1 mM. The CTAB solution was added to the calcium carbonate liquid crystal microsphere system. In the mixed system, the final concentration of CTAB was 1 mM and the concentration of the calcium carbonate liquid crystal microspheres was 0.2 mM. The mixture was mixed for 30 minutes at a magnetic stirrer speed of 1000 rpm, and then an emulsion of CCT modified with CTAB was obtained, which was named an optical sensor of calcium carbonate liquid crystal microspheres (CTAB-CCT).
[0105] 3.1 Adsorption experiment of CTAB-CCT optical biosensor on HSA / BSA
[0106] HSA and BSA were prepared into solutions of different concentrations using PBS buffer at pH 7.4. Then a certain concentration of CTAB-CCT was added and incubated for 30 minutes. After the reaction was completed, the solution was aspirated with a dropper and dropped onto a glass slide, which was then transferred to a POM for observation.
[0107] 3.2 Specificity experiment of CTAB-CCT optical biosensor
[0108] Sodium chloride, ferrous chloride, glucose and L-glutamine were prepared into 1 mg / mL solutions with PBS buffer at pH 7.4. Then a certain concentration of CTAB-CCT was added and incubated for 30 minutes. After the reaction was completed, the solution was aspirated with a dropper and dropped on a glass slide, and then transferred to POM for observation.
[0109] 3.3 Cell culture
[0110] MCF-7 cells were cultured in a medium containing 10% FBS and 1% penicillin-streptomycin (10000 U mL -1 ) in DMEM medium, and the cells were cultured in an incubator at 37°C and 5% CO2. When the cells grew to about 80%, the medium was discarded and the cells were rinsed once with PBS (0.01M, pH=7.4) to remove non-adherent or aged cells. Then, 1 mL of trypsin EDTA (0.25%) was added to the culture dish to digest the cells for 1 to 2 minutes. The cells were collected by centrifugation (800r / min, 3min) and dispersed in a special culture dish for cell culture.
[0111] 3.4 Cytocompatibility experiment of CTAB-CCT optical biosensor
[0112] MCF-7 cells were seeded in the corresponding growth medium in six-well plates and allowed to adhere for 3 h. The medium was then removed from the wells using a pipette. CTAB-CCT (sterilized under UV light overnight) was suspended in cell culture medium at different concentrations (0.1 mg / mL) and then added to the wells containing cells (≈1×10 6 Cell mL -1 ). Cells without CTAB-CCT were used as a control group. Cells were grown at 37°C for 12 h in a humidified environment of 95% air and 5% CO2. The culture medium was then removed and the cells were gently rinsed with PBS. Calcein AM (10 μL) and propidium iodide PI (15 μL) were mixed in PBS (5 mL) and added to the cells. The cells were allowed to stain for 25 min at 37°C in a humidified environment of 95% air and 5% CO2. The PBS was then gently removed with a pipette, the cells were rinsed with fresh PBS, and cell culture medium was added to allow for a longer period of time for effective analysis. Live / dead cells were then observed using a fluorescence microscope.
[0113] 3.5 CTAB-CCT optical biosensor imaging experiments in living cells
[0114] For the cells cultured in step 3.3, the culture medium in the culture dish was aspirated and replaced with a mixed solution of DMEM and PBS containing different concentrations of HSA (volume ratio 1:1). Then CTAB-CCT with a final concentration of 100 μg / mL was added, and the cells were incubated for 25 minutes to observe the phenomenon.
[0115] Fig. 22 Schematic diagram of the working principle of CCT-based biosensor.
[0116] First, the orientation behavior of CTAB-CCTs in human serum albumin (HSA) solution was studied. Since the previous experiment proved that CTAB-CCT can maintain its radial configuration under pH = 7.4, the subsequent experiments were carried out under this condition. Fig.23 As shown, Fig.23 In the figure, (a) is the optical image of CTAB-CCT before and after adding 1 mg / mL HSA solution, (b) is the Zeta potential of CTAB-CCT and after adding HSA / BSA (each 1 mg / mL); POM photos and microscope bright field photos show ( Fig.23 (a) shows that when CTAB-CCTs are dispersed in PBS buffer (pH = 7.4), they present a radial configuration before contacting SA. Interestingly, it can be seen under POM and bright field microscopy that after contacting SA (1 mg / mL) dissolved in buffer, the central topological defects of CTAB-CCTs move toward the two poles, forming a so-called bipolar configuration. Zeta potential measurements confirmed the binding of CTAB-CCTs to SA: First, these positively charged CTAB-CCTs (+11.70 mV) complexes show strong binding to serum albumin (BSA / HSA) (BSA: -25.10 mV / HSA: -23.20 mV). Due to their low isoelectric points (BSA: 4.8, HSA: 4.7), they are negatively charged under neutral conditions. As expected, the resulting BSA-CTAB-CCTs (-17.20 mV) and HSA-CTAB-CCTs (-14.90 mV) complexes both showed a net negative charge, confirming that serum albumin was successfully bound to the surface of the CTAB-CCT complexes.
[0117] Fig.24 In the figure, (a) is the CLSM image after CTAB-CCT was incubated with 1 mg / mL FITC-labeled HSA, and (b) is the fluorescence intensity image after CTAB-CCT was incubated with 1 mg / mL FITC-labeled HSA. Fig.24 As shown in the figure, after adding 1 mg / mL FITC-labeled HSA (final concentration) to PBS buffer with a pH of 7.4, the cells were incubated with CTAB-CCTs for 30 min to obtain confocal images. The strong green fluorescence signal on the surface of CTAB-CCTs confirmed the adsorption of HSA on the surface of CTAB-CCTs ( Fig.24 The fluorescence spectrum can also confirm this effect ( Fig.24 (as shown in (b)).
[0118] Then, the time required for CTAB-CCTs to complete the configurational transformation after adding HSA was investigated. Fig.25 As shown, Fig.25 POM images of the radial-bipolar configuration and the intensity distribution of the radial-bipolar deformation of CTAB-CCT after exposure to HSA buffer at pH = 7.4 for different time periods. Fig.25 In the figure, the upper row of pictures are POM pictures, and the lower row of pictures are intensity distribution pictures. Fig.25 As shown: CTAB-CCT was placed in a HSA buffer solution at pH = 7.4, where the HSA concentration was 100 μg / mL to evaluate its configuration transformation process over time. As time went on, HSA continued to adsorb onto the surface of CTAB-CCT, and the initial radial configuration of CTAB-CCT slowly transformed into a pre-radial, pre-bipolar, and finally a bipolar configuration. The entire transformation process took about 25 minutes, at which time all CCTs had completed the transformation. Therefore, the optimal incubation time was determined to be 25 minutes.
[0119] Since deviations from normal HSA concentrations in serum are associated with several diseases, the next goal was to investigate the sensitivity of CTAB-CCT droplets to various concentrations of HSA. Fig.26 The POM images and bright field images of CTAB-CCT after exposure to HSA solutions of different concentrations are shown. The exposure time (25 min) is kept constant here, including (a) 2 mg / mL, (b) 1 mg / mL, (c) 500 μg / mL, (d) 100 μg / mL, (e) 50 μg / mL, and (f) 1 μg / mL. It was found that HSA as low as 100 μg / mL caused the configuration transformation of all CTAB-CCTs. However, as the concentration decreased, at a concentration of 5 μg / mL of HSA, bipolar, pre-radial, and radial CTAB-CCT particles coexisted, while at a concentration as low as 1 μg / mL, all CTAB-CCTs maintained the radial configuration unchanged. Therefore, the use of CTAB-CCTs can reflect the presence of HSA in the solution environment.
[0120] The optical sensor constructed based on the cationic surfactant CTAB adsorbed on the sensitive surface of CCT can achieve rapid, sensitive and intuitive imaging of electronegative proteins. The obtained data are analyzed, such as Fig. 27 As shown, Fig. 27 In the figure, (a) is a diagram of the configuration conversion rate of CTAB-CCTs exposed to HSA buffer solutions of different concentrations, and (b) is a calibration curve of HSA concentration obtained using the configuration conversion rate of CTAB-CCTs (mean standard deviation; n=3); Fig. 27As shown in the figure, when the concentration of HSA is as low as 5μg / mL, a small part of the CTAB-CCT configuration shows changes. It was also found that the error of the output optical signal was small, indicating that the sensor can give an accurate analysis of the presence of HSA. The POM graph obtained during the detection has good stability, and the lower limit of the optical imaging of HSA by CTAB-CCT can reach 5μg / mL. The calibration curve of HSA concentration was obtained using the CTAB-CCTs configuration conversion rate as shown in the figure below. Fig. 27 As shown in (b), the linear regression equation y=0.96x+3.45 is obtained, where y is the configuration conversion rate of CTAB-CCTs and x is the concentration of HSA. It can be seen that when the concentration of HSA is in the range of 0-100 μg / mL, the configuration conversion rate of CTAB-CCTs has a linear relationship.
[0121] In the presence of metal ions (Na + and Fe 2+ ) and biomolecules (glucose and L-glutamine), the selectivity of CTAB-CCTs for detecting HSA / BSA was evaluated. Fig.28 As shown, Fig.28 The POM images and corresponding bright field microscopy images of CTAB-CCTs exposed to 1 mg / mL buffer solutions of different substances. Fig.28 In, (a) and (e) are Na + , (b) and (f) are Fe 2+ , (c) and (g) are glucose, (d) and (h) are L-glutamine, (i) and (k) are HSA, and (j) and (l) are BSA. Fig.28 As shown, CTAB-CCTs were + , glucose and L-glutamine solutions, but in the presence of Fe 2+ In the solution of Fe 2+ The connection with two adjacent -O- groups on the surface of CTAB-CCTs may change the arrangement of particles on a small part of the surface of CTAB-CCTs, leading to a configuration change. This result proves that the sensor has good selectivity for electronegative proteins.
[0122] Next, the biocompatibility of CTAB-CCTs was investigated to facilitate its application in sensing the cell microenvironment. As we all know, CaCO3 is an important component of biominerals and has good biocompatibility. Human breast cancer cells (MCF-7) were selected as model cells. Fig.29 As shown, Fig.29The survival of MCF-7 cells before and after the addition of CTAB-CCTs. The control group is cells without CTAB-CCT treatment. Fig.29 It was shown that, compared with the control group (cells cultured in medium without the addition of CTAB-CCTs), approximately 99.9% of the cells survived when the CTAB-CCTs concentration was 100 μg / mL.
[0123] The cell survival rate remained above 99%, indicating that CTAB-CCTs is highly cell-compatible. This provides a good basis for its use as a cell sensor. Here, a CTAB-CCTs concentration of 100 μg / mL was selected for further experiments, because a higher concentration may cause a lot of CTAB-CCTs to wrap around the cell surface, hindering normal cell activity.
[0124] In previous selective experiments, it has been demonstrated that the main components of DMEM (glucose and L-glutamine) have no effect on the CTAB-CCT sensor. Fig.30 As shown, Fig.30 For CTAB-CCTs, different concentrations of HSA outside of MCF-7 cells were imaged, as Fig.30 As shown in the figure, CTAB-CCT with a concentration of 0.1 mg / mL was co-incubated with MCF-7 cells in DMEM+PBS (volume ratio 1:1) containing different concentrations of HSA and pH = 7.4 for 30 minutes, and the efficiency of CTAB-CCT in detecting HSA was analyzed. When the HSA concentration in the control group was 0, the radial configuration of CTAB-CCT around MCF-7 cells remained unchanged over time. When the HSA concentration reached 500 μg / mL, a gradual change of RB was observed on CTAB-CCT, and finally CTAB-CCT showed a mixed configuration of radial and bipolar coexistence. This result is different from the previous phenomenon of imaging HSA in PBS solution. The reason is that when MCF-7 cells were co-incubated with CTAB-CCT, they also took up some HSA, which actually reduced the overall HSA concentration and failed to complete the conversion of the configuration of CTAB-CCT. When the HSA concentration reached 1000 μg / mL, all conformational changes of CTAB-CCT were observed, indicating that the concentration of HSA in the extracellular solution at this time was sufficient to enable CTAB-CCT to complete the overall conformational transformation.
[0125] This invention demonstrates the first CCT-based system to study the adsorption of proteins on interfaces, changing their optical morphology to achieve the purpose of imaging proteins. It also provides a new presentation mode for the interaction between CTAB and serum albumin. This work will not only enhance the understanding of various interfacial phenomena, but also provide a basis for the design of CCT-based biosensing interfaces.
[0126] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect, characterized in that: The following steps are involved: dissolving a water-soluble calcium salt to obtain a calcium salt solution; Using ammonium carbonate as a diffusion gas source, the calcium salt solution undergoes a gas diffusion reaction to obtain a calcium carbonate liquid crystal microsphere system; The calcium carbonate liquid crystal microsphere system is mixed with a cationic surfactant and modified to obtain the biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect; The dissolving agent comprises a mixed solvent of water and ethylene glycol; the volume ratio of water to ethylene glycol in the mixed solvent of water and ethylene glycol is 1:3 to 1:6; The water-soluble calcium salt includes one or more of calcium chloride, calcium nitrate and calcium hydroxide, and the concentration of the calcium salt in the calcium salt solution is 30 to 50 mmol / L; The ratio of the amount of ammonium carbonate to the amount of calcium salt in the calcium salt solution is ≥ 1:1; The gas diffusion reaction time is 3h to 24h; After the gas diffusion reaction, the product obtained by the gas diffusion reaction is centrifuged, and the lower layer of liquid is taken as the calcium carbonate liquid crystal microsphere system; The ratio of the amount of calcium carbonate microspheres to the amount of cationic surfactant in the mixed system is 1:5 to 1:10; The concentration of the cationic surfactant in the mixed system is 1 mM; The solvent of the cationic surfactant is a PBS solution with a pH of 7.4; The number of carbons in the carbon chain of the cationic surfactant is 16 to 18; the cationic surfactant includes one or more of hexadecyltrimethylammonium bromide, heptadecyltrimethylammonium bromide and N,N-dimethyl-N-octadecyl-3-aminopropyltrimethoxysilyl chloride.
2. The preparation method according to claim 1, characterized in that: The modification temperature is room temperature and the modification time is 30 minutes to 1 hour.
3. A biocompatible calcium carbonate-based liquid crystal material having an electro-optical effect obtained by the preparation method according to any one of claims 1 to 2.
4. Use of the biocompatible calcium carbonate-based liquid crystal material having electro-optical effect as claimed in claim 3 in protein detection.
Citation Information
Patent Citations
Preparing method for oil-based hydroxyapatite colloidal crystals
CN105417514A
Hollow-structured mesoporous silica material and preparation process
US20050244322A1